2016
DOI: 10.1186/s12984-016-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity outside of structured therapy during inpatient spinal cord injury rehabilitation

Abstract: BackgroundLittle information exists on the content of inpatient rehabilitation stay when individuals with spinal cord injury (SCI) are not engaged in structured rehabilitation therapy sessions. Investigation of inpatient therapy content is incomplete without the context of activities outside of this time. We sought to quantify physical activity occurring outside of physical therapy (PT) and occupational therapy (OT) sessions during inpatient SCI rehabilitation and examine how this activity changes over time fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
(39 reference statements)
2
22
0
1
Order By: Relevance
“…With the surge in evidenced-based motor rehabilitation practice, one of the main hurdles for effective translation of neuro-rehabilitative motor therapies into the community is the limited amount of time spent by patients in rehabilitation clinics ( Newitt et al, 2016 ). To combat this limitation, carefully designed feedback based home-therapy programs have indeed become an integral part of modern evidence-based neuro-rehabilitation practice ( Buick et al, 2016 ; Zbogar et al, 2016 ). The successful development of the tES technique presented herein can operate autonomously for extended periods of time in unrestrained rats, allowing its use as a long-term therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
“…With the surge in evidenced-based motor rehabilitation practice, one of the main hurdles for effective translation of neuro-rehabilitative motor therapies into the community is the limited amount of time spent by patients in rehabilitation clinics ( Newitt et al, 2016 ). To combat this limitation, carefully designed feedback based home-therapy programs have indeed become an integral part of modern evidence-based neuro-rehabilitation practice ( Buick et al, 2016 ; Zbogar et al, 2016 ). The successful development of the tES technique presented herein can operate autonomously for extended periods of time in unrestrained rats, allowing its use as a long-term therapeutic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring functional activities and the context where they take place could also be used to remind patients of staying active: in a recent work, Zbogar and colleagues 23 measured physical activity levels outside of physical therapy sessions in SCI inpatients using a wrist monitor and a self-report questionnaire. They found that activity levels measured by steps increased significantly from admission to discharge, while self-report measures did not show any change.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,41 Further, it is a walking measure that has been reported to change in response to inpatient SCI rehabilitation. 42 The disadvantage of the 10MWT, however, is that it is appropriate only for those individuals with SCI who can walk without the assistance of another person (i.e. stage 3B or greater on the SWAT).…”
Section: C Community Ambulatormentioning
confidence: 99%